The evolution of economic integration systems in French West Africa: the CEAO case - (:unkn) unknown (My University, 1991)
From more than thirty years, the French West African states have been trying to achieve the integration of their economies. An analysis of the different attempts at integration shows a shifting tendency towards the liberal reference model. by introducing more varied reponses based on progressivity, selectivity and flexibility towards the question of customs deregulation, and by arranging the distribution of costs and advantages according to the principle of compensatory equity, the organised exchange zone (OEZ), on the recommendations of the CEAO, is challenging the free-trade rules adhered to bu the UDAO and the UDEAO. Unfortunately, this evolution, more sensitive to local differences and the gradual reduction of development inequalities, does not completely show through in the integration mechanisms: legal adjustments show a backward trend towards the reinforcement of unilateralism, whilst economic instruments, although innovative, remain so ineffectual that they cannot claim to represent the ideal of solidarity. This hiatus which is slowing the development of the integration process has a negative effect on its results, which have failed to reach the defined objectives. it is necessary to eliminate such an obstacle even more so since regional integration has become more important than ever. This will be possible through the emergence of a true central community axis and the establishment of genuine community practices.
Keywords: African Research